Do teatro do oprimido à teatra da oprimida: um convite à noção da periculosidade - RIBEIRO, Gabs Almeida (2024)
This article entitled “From the Theater of the Oppressed to the Theater of the Oppressed: an invitation to the notion of dangerousness” raises a special question and brings my concerns from my academic experiences in the Full Degree course in Theater at the UFPA School of Theater and Dance, where I seek a reflection, based on experiences and studies from the theoretical field of Aesthetics of the Oppressed (BOAL, 2009), the work “Teatra Da Oprimida” (LEAL, 2019) and the “Pedagogies of Travestilities” (PASSOS, 2022), which aim to question the absence of transgenderities as a theoretical reference in the course. I end with the proposal of a political act, which aims to provoke a reflection on the transgressive potential of the theoretical field that discusses and deepens, and at the same time makes resistance and struggles of trans/transvestites as subject to rights.